STUDI PATOGENITAS METARHIZIUM ANISOPLIAE (METCH.) SOR HASIL PERBANYAKAKAN MEDIUM CAIR ALAMI TERHADAP LARVA ORYCTES RHINOCEROS (THE PATHOGENICITY STUDY OF METARHIZIUM ANISOPLIAE (METCH.) SOR. AS A PROPAGATION RESULT IN NATURAL LIQUID ON THE ORYCTES RHINOCE - Heriyanto, Heriyanto; Suharno, Suharno (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2008)
The application of entomopathogen fungus in pest control is a part of Integrated Pest Control componen. Metarhizium anisopliae is an entomopathogen which able to infected the Oryctes rhinoceros larve so it require to be developed in the field by using the simple technology according the materials an equipments owned by the farmer. The research about Metarhizium anisopliae fungus which has just being isolated for a month from its host, then being propagated in medium of Alyoshina liquid, corn extraction, potato extraction, casave extraction, and applicated in larve cultivation web, shows the same pathogenicity after 30 days from application. The fungus propagation in Alyoshina medium shows the faster growth (10.39 cm2/7 days), much spores production (33.29 x 107spores/ml/7 days) and short lethal time 50 (13.6 days) and there is significantly influence than the other treatments. While the spore size include the length of 6.09-6.66 micrometers and width of 2.75-3.06 micrometers is no significantly influence between treatmens. The Metarhizium anisopliae can be propagated in natural liquid medium by using the simple fermentor, so obtained much spores in the short time.